2000
DOI: 10.1177/0146167200268003
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Evaluation from Description in the Personality-Emotion Relationship

Abstract: Personality characteristics and emotional experiences contain both descriptive and evaluative aspects. The purpose of the present study was to test whether evaluation was a mediator in two well-established personality-emotion relationships. Using structural equation modeling procedures with two samples of participants, the authors demonstrated that evaluation fully mediated the relationship between neuroticism and negative affect and partially mediated the relationship between extraversion and positive affect.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 41 publications
(57 reference statements)
0
23
0
Order By: Relevance
“…A great deal of research has examined the associations between the Big Five personality traits and positive and negative affect at the trait level. The most intensively studied associations between personality and affect have been the associations between extraversion and positive affect and neuroticism and negative affect (Charles, Reynolds, & Gatz, 2001;Costa & McCrae, 1980a;David, Green, Martin, & Suls, 1997;DeNeve & Cooper, 1998;Diener, Oishi, & Lucas, 2003;Diener, Suh, Lucas, & Smith, 1999;Fossum & Barrett, 2000;Gross, Sutton, & Ketelaar, 1998;Izard, Libero, Putnam, & Haynes, 1993;Larsen & Ketelaar, 1989, 1991Lucas & Fujita, 2000;McCrae & Costa, 1991;Meyer & Shack, 1989;Rusting, 1999;Schutte, Malouff, Segrera, Wolf, & Rodgers, 2003;Spain, Eaton, & Funder, 2000;Suh, Diener, & Fujita, 1996;Watson & Clark, 1992). One meta-analysis found that extraversion correlated 0.37 with positive affect (Lucas & Fujita, 2000).…”
Section: Associations Between Personality and Affect: Trait Vs Statementioning
confidence: 99%
“…A great deal of research has examined the associations between the Big Five personality traits and positive and negative affect at the trait level. The most intensively studied associations between personality and affect have been the associations between extraversion and positive affect and neuroticism and negative affect (Charles, Reynolds, & Gatz, 2001;Costa & McCrae, 1980a;David, Green, Martin, & Suls, 1997;DeNeve & Cooper, 1998;Diener, Oishi, & Lucas, 2003;Diener, Suh, Lucas, & Smith, 1999;Fossum & Barrett, 2000;Gross, Sutton, & Ketelaar, 1998;Izard, Libero, Putnam, & Haynes, 1993;Larsen & Ketelaar, 1989, 1991Lucas & Fujita, 2000;McCrae & Costa, 1991;Meyer & Shack, 1989;Rusting, 1999;Schutte, Malouff, Segrera, Wolf, & Rodgers, 2003;Spain, Eaton, & Funder, 2000;Suh, Diener, & Fujita, 1996;Watson & Clark, 1992). One meta-analysis found that extraversion correlated 0.37 with positive affect (Lucas & Fujita, 2000).…”
Section: Associations Between Personality and Affect: Trait Vs Statementioning
confidence: 99%
“…Affect and personality are known to be correlated (Carver, Sutton, & Scheier, 2000;Fossum & Feldman Barrett, 2000;Gross, Sutton, & Ketelaar, 1998;Lucas & Fijita, 2000;Moskowitz, Brown, & Côté, 1997). The superfactors of Extraversion and Neuroticism, for example, yield robust relations to affect (Costa & McCrae, 1980Diener & Emmons, 1984;Izard, Libero, Putnam, & Haynes, 1993;McCrae & Costa, 1991;Meyer & Shack, 1989;O'Malley & Gillett, 1984;Thayer, Takahashi, & Pauli, 1988;Warr, Barter, & Brownbridge, 1983;Watson & Clark, 1992, 1997Williams, 1981;Yik & Russell, 2001;Yik, Russell, Ahn, Fernández Dols, & Suzuki, 2002).…”
Section: On the Relation Between Affect And Personalitymentioning
confidence: 99%
“…Various questions arise about the relation of affect to personality (e.g., Allik & Realo, 1997;Carver, Sutton, & Scheier, 2000;Fossum & Feldman Barrett, 2000;Gross, Sutton, & Ketelaar, 1998; Lucas & Fijita, 2000;Moskowitz, Brown, & Côté, 1997).…”
Section: Predicting Affect From Personalitymentioning
confidence: 99%